Laparoscopic cystogastroanastomosis in a pediatric patient: a case report. - Vera Portilla, Angel F (2021)
The pancreatic disorders, as acute pancreatitis, of biliary etiology are rare in pediatrics, even more the pancreatic pseudocysts. They are liquid collections surrounded of a fibrous capsule without epithelium, secondary to acute pancreatitis. We present the case of a 14-year-old female patient with a history of acute pancreatitis because of biliary etiology, 10 months prior. She complained of intermittent abdominal pain and a palpable mass in the epigastrium. The Imaging studies showed a pancreatic pseudocyst and cholelithiasis. The laparoscopy was chosen because the technical and esthetic benefits for this population. Therefore, a laparoscopic cystogastro-ostomy-anastomosis and cholecystectomy were performed, with good progress. We affirm this technique is a safe and effective method for the management of this pathology in pediatric patients, and it should be considered as the first option in case endoscopic procedures are not available. This is the first report in our settings.